Understanding the Spectrum of SLC2A1-Associated Disorders - Marytery Fajardo; Melissa L. Cirillo (Pediatric Neurology Briefs Publishers, 2017)
Investigators from the Danish Epilepsy Center the frequency of SLC2A1 mutations in a cohort of patients with different types of epilepsies.